2021
DOI: 10.1017/s0263574721001430
|View full text |Cite
|
Sign up to set email alerts
|

Impedance matching control between a human arm and a haptic joystick for long-term

Abstract: An impedance matching control framework between a human and a haptic joystick for long-term teleoperation is proposed in this research. An impedance model of the human arm is established analyzing the characteristics of human perception, decision, and action. The coefficients of the human arm’s impedance have been identified using a least squares method. The human arm’s impedance matching algorithm generates a corresponding motion vector for the human arm, which is determined by the interaction force measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…In summary, assistive robotics technology has demonstrated its effectiveness in enhancing autonomy and aiding elderly and disabled individuals [22]. Studies have reported a 40% increase in daily activities and a 30% reduction in caregiver demands [23,24]. When comparing commercially available devices with those under development and various innovative approaches in robotic meal assistance solutions, it becomes evident that commercial manipulators offer established solutions characterized by high costs.…”
Section: Introductionmentioning
confidence: 99%
“…In summary, assistive robotics technology has demonstrated its effectiveness in enhancing autonomy and aiding elderly and disabled individuals [22]. Studies have reported a 40% increase in daily activities and a 30% reduction in caregiver demands [23,24]. When comparing commercially available devices with those under development and various innovative approaches in robotic meal assistance solutions, it becomes evident that commercial manipulators offer established solutions characterized by high costs.…”
Section: Introductionmentioning
confidence: 99%
“…Control strategies are crucial to achieve maximum performance and confidence and improving ergonomics [18], flexibility [19], accuracy, and repeatability [20]. pHMI-based technologies often focus on force control methods such as admittance control [21][22][23], impedance control [9,24,25], and direct force control [26]. Simpler design choices could be discarded over more complex control strategies involving adaptiveness [27,28], robustness [29][30][31], and predictiveness.…”
Section: Introductionmentioning
confidence: 99%
“…In our prior pHHI study, we examined human control strategies in a manner applicable to design of robot controllers, demonstrating that a mechanical impedance model can characterize methods to aid balance 15 . pHRI research in upper limb manipulation has shown that varying robot impedance based on human impedance can improve task performance [16][17][18][19] and reduce interaction forces 16,17,20 and mechanical work 21 , but these impedance modulation strategies have yet to be examined in the context of pHHI during gait.…”
Section: Introductionmentioning
confidence: 99%